Conflictividad política, pandemia de COVID-19 y nuevos paradigmas - Villasmil Espinoza, Jorge Jesús (Cuestiones Políticas, 2020)
Everything indicates that the year 2020 will end up signified by high levels of political conflict that set up an international scenario of exponential entropy with testimonies for order and global stability. Add to that the economic and social havoc generated by the pandemic of the new coronavirus, the outlook for 2021 is not encouraging at all. However, the question for social scientists and philosophers in general is these events to shape new political, economic and sociocultural paradigms in the world? The objective of reflections lies in presenting in the special issue, Vol. 38, II part, and at the same time analyzing the scenarios of political conflict in the real world in the context of COVID-19. The conclusion highlights the fact that, despite the expectations of social justice, sorrow and human rights of much of human societies, the theoretical and epistemological elements necessary to shape new or at least models of political, economic and social organization beyond social and liberal trajinisms are not apparent from what academic elites see.